Pengaruh Kompetensi dan Integritas Auditor Internal serta Whistleblowing System terhadap Fraud Prevention - Maria Stephanie Dengah; Andre Syukri Putranto; Haryono Umar (Sekolah Pascasarjana Perbanas Jakarta, 2021)
Fraud is still a phenomenal and interesting issue to discuss with cases that are currently developing in society and fraud is also considered as one of the problems that pose serious challenges for all types of organizations. This study aims to examine and analyze the influence of internal auditor competence and integrity, also whistleblowing systems for fraud prevention. This study uses primary data by distributing structured questionnaires via google form to internal auditors at the Inspectorate General and Secretariat General of the Ministry of Finance in Jakarta. The questionnaire contains questions that have covered each of the assessment indicators. The statistical method used is multiple regression analysis using SPSS 25 to determine the direct or indirect effect of the independent variable on the dependent variable. The results of this study found that the competence of internal auditors affects existing fraud prevention, while integrity and whistleblowing systems do not affect fraud prevention.